Efektivitas model pembelajaran guided discovery learning terhadap hasil belajar matematika siswa pada materi peluang kelas VIII SMP Negeri 2 Wonggeduku - Irmayanti; Hermanto; Hajeniati, Nining (Jurnal Pendidik Indonesia, 2022)
This study used the guided discovery learning model to (1) determine students' mathematics learning outcomes in class VIII probability material at SMP Negeri Wonggeduku. (2) to determine the effectiveness of the guided discovery learning model on students' mathematics learning outcomes in class VIII opportunity materials at SMP Negeri Wonggeduku. The type of research used is a quasi-experimental or (quasi-experimental) research design with a nonequivalent posttest-only control group design. The number of samples in the study was 50, divided into 25 samples for the experimental class and 25 for the control class. The sampling technique is random sampling. The data collection technique is a written test. There are two data analysis techniques, namely descriptive analysis and inferential analysis. The descriptive analysis results showed that the experimental class's average learning outcomes, with a value of 70,83, were higher than the control class, with a value of 63,06. In contrast, the results of the inferential analysis obtained the value of t count = 2,178 > tel 1,677. So, the research test shows that ho is rejected, H0 is rejected, and H1 is accepted. Namely, the average mathematics learning outcomes of students who receive guided discovery learning models are more effective than students who receive conventional learning.